BENTUK TARI KEMBANG KEMANGI KARYA JAJULAIDIK DAN YUDA GADIS OCTIANI SANGGAR TARI SAYUWIWIT - Anggraini, Maya Lestari; Slamet (Greget : Jurnal Kreativitas dan Studi Tari, 2024)
This research describes the form and choreography of the Kembang Kemangi dance by Jajulaidik and Yuda Gadis Octiani from the Sayuwiwit Dance Studio. Kembang Kemangi dance is the new choreography inspired by the local tradition of Banyuwangi. The research questions include: (1) What is the form of the Kembang Kemangi dance by Jajulaidik and Yuda Gadis Octiani from the Sayuwiwit Dance Studio, (2) How is the choreography of the Kembang Kemangi dance by Jajulaidik and Yuda Gadis Octiani from the Sayuwiwit Dance Studio. In dissecting the formulation of the problem in this research, the theory of form and choreography by Slamet, in his book entitled "Melihat Tari," was used. This research uses a qualitative research method with a choreographic approach. The research steps are data collection through observation, interviews, literature review, and data analysis. The results of the research show that the form of the Kembang Kemangi dance consists of dance elements. These are movement, music, makeup and costume, dancers, flour pattern, and stage. Kembang Kemangi is a group choreography that contains 7 dancers.  The choreography of the dance movements is related to "solah-ebrah." Solah is an effort to manifest the form of human body movements that are developed to form an ebrah which includes a variety of movements that have the essence of the smallest unitary meaningful motion form.